Perceptions of registered nurses regarding factors influencing service delivery in expanding programmes in a primary healthcare setting - Nnoi. A. Xaba; Mmapheko D. Peu; Salaminah S. Phiri (AOSIS, 2012)
The aim of this study was to explore and describe the perceptions of registered nurses regarding factors influencing service delivery regarding expansion programmes in a primary healthcare setting, using a qualitative approach. The registered nurses, who have been working in the clinics for more than two years and have been exposed to the expansion programmes there, were purposively sampled. Two focus group interviews were conducted in a neutral place and the data collected by the researcher Nnoi A. Xaba (N.A.X.). Data were analysed by the researcher and an independent co-coder using the Tesch method. Categories, subcategories and themes were identified; those that formed the basis of discussion were disabling factors, enabling factors, client-related factors, service-related factors and solutions to problems. It is recommended that integration of programmes and coordination be done at a provincial level and planned together with the training centres in order to alleviate problems in service delivery. Training on expansion programmes in the form of in-service education should be carried out continually in the region. Die doel van die studie was om die persepsie van geregistreerde verpleegkundiges met betrekking tot die  faktore wat dienslewering van die uitbreidingsprogramme in 'n primêre gesondheid opset beinvloed; te eksploreer en te beskryf. 'n Kwalitatiewe benadering is gevolg in die iutvoering van die studie. 'n Doelgerigte steekproef is uitgevoer vanuit geregistreerde verpleegkundiges wat vir langer as twee jaar in die klinieke werksaam was en blootgestel is aan die uitbreiding programme. Twee fokus groep onderhoude is deur die navorser Nnoi A. Xaba (N.A.X.) in 'n neutrale opset uitgevoer. Data is deur die navorser en ŉ onafhanklike kodeerder ontleed volgens Tesch se metode van analise. Kategorieë, sub-kategorieë en temas was geidentifiseer. Die kategorieë fundamenteel tot die bespreking behels: remmende faktore, bydraende faktore, kliënt-verwante faktore, diens-verwante faktore, en oplossing van probleme. Daar word aanbeveel dat die integrasie en koordinasie van programme op provisiale vlak beplan word in samewerking met opleidings instansies om die dienslewerings probleem te verlig. In die streek behoort opleiding met betrekking tot die uitbreidingsprogramme deurlopend deur middel van indiensopleiding gedoen word.